Occurrence of Flux Jumps in MgB2 Bulk Magnets during Pulse-Field Magnetization. (June 2020) - Sakai, N; Oka, T; Yamanaka, K; Dadiel, L; Oki, H; Ogawa, J; Fukui, S; Scheiter, J; Häßler, W; Yokoyama, K; Noudem, J; Miryala, M; et al.
Abstract: The magnetic flux capturing of MgB2 bulk magnets made by spark plasma sintering process has been precisely investigated to clarify the mechanism of flux motions during the pulse-field magnetization processes. The field trapping ratio B T / B P was evaluated as a key parameter of field trapping ability which strongly relates to the heat generation due to the rapid flux motion in the samples. The time dependence of magnetic flux density revealed the actual flux motion which penetrated the samples. The trapped fields B T and field trapping ratios B T / B P of various samples were classified into three regions of 'no flux flow', 'fast flux flow' and 'flux jump' according to the generation of heat and its propagation. A flux jump was observed late at 280 ms from the beginning of PFM process, while the field penetration B P showed its peak at 10 ms. Considering the heat propagation speed, the long-delayed flux jump should be attributed to the macroscopic barriers against the heat propagation to the surface centre of bulk magnet.